Investigating Online Learning Versus Face-To-Face Instruction and It’s Impact on Students’ Listening Comprehension - Qomariyah, Siti Syafi'atul; Nafisah, Bq Zuhrotun (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Most people agree that one of hardest talents to master is listening comprehension because learners must analyse spoken word instantly while understanding meaning, vocabulary, pronunciation, and contextual information simultaneously. In the past few, the increasing use of online learning has led to ongoing debate regarding whether online instruction is as effective as traditional face-to-face instruction in developing listening comprehension. Therefore, this study aimed to investigate the effect of online versus face-to-face instruction on EFL students’ listening comprehension. This study employed a quasi-experimental pre-test–post-test non-equivalent control group design. The participants were 130 first-semester students of the English Language Education Department, Mandalika Univesity of Education. Two intact classes were selected purposively, consisting of an experimental group receiving online instruction and a control group receiving face-to-face instruction. The treatment was conducted over six instructional meetings. The instrument was a listening comprehension test consisting of multiple-choice items measuring main ideas, specific information, and implied meaning. Instrument validity was established through expert judgment and item analysis, while reliability testing using Cronbach’s Alpha a coefficient of 0.82, indicating high internal consistency. The data were analysed using descriptive and non-parametric inferential statistics because the data violated normality and homogeneity assumptions. The Wilcoxon Signed-Rank Test revealed significant improvement in both the experimental group (Z = -4.60, p < .001) and the control group (Z = -4.50, p < .001). However, the Mann–Whitney U Test showed no statistically significant difference between the two instructional groups (p = .143 > .05). The findings indicate that both online versus face-to-face instruction effectively improved students’ listening comprehension, but neither instructional mode demonstrated statistically superior outcomes within the context of this study. The results suggest that instructional quality, meaningful listening input, learner engagement, and effective learning design may play a more important role in listening comprehension development than instructional delivery.